PERMASALAHAN SENGKETA TANAH MASYARAKAT TERKAIT KEPEMILIKAN HAK TANAH DALAM PEMBANGUNAN JALAN DI KELURAHAN WEWELEN KECAMATAN TONDANO BARAT KABUPATEN MINAHASA - Agustien Cherly Wereh; Enjeli Yuliana Lumaing; Puteri Dewi Sari Pinem; Yesika Sapira BR Sembiring; Romi Mesra (Labor Program Studi Pendidikan Sosiologi, 2022)
In the Wewelen Sub-District, there are 2 families, namely the Laluan-Sakul Family and the Aguw Family, who have problems regarding land disputes which are quite protracted and often recur, so they need a settlement as soon as possible. The research approach used is qualitative research. Qualitative research is a type of research that is understood as research that utilizes descriptive data. While the data used is descriptive data in the form of data in the form of sentences both verbal and non-verbal. Data collection techniques used are interviews, observation, documentation. The results of this study concluded that the problem of community land conflicts in Wewelen Village, Tondano Barat District, Minahasa Regency occurred because of conflicts in road construction, land stake boundaries and land conflict resolution carried out through local government mediation